Identifying the significance of a Foot and Mouth Disease outbreak on the South African beef industry - Jordaan, Daniel du Plessis Scheepers (University of Pretoria, 2024)
Mini Dissertation (MSc Agric (Agricultural Economics))--University of Pretoria, 2023.